2017
DOI: 10.1111/jopr.12723
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Static Articulation Accuracy of Virtual Models – Part I: System Trueness and Precision

Abstract: The overall interarch global distortion of all three model scanner-CAD systems was low and did not exceed 0.6%. Variations in scanner technology, virtual articulation algorithm, and use of physical articulators contributed to the differences in distortion observed among all three groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…Several studies investigated the clinical utility of static digital articulation . Gartner and Kordass compared mechanical and virtual articulators by analyzing contact point patterns at maximum intercuspation, but did not analyze individual condylar or other articulator settings in detail and did not test alterations to those settings, finding no significant difference between the mechanical and virtual articulators .…”
mentioning
confidence: 99%
“…Several studies investigated the clinical utility of static digital articulation . Gartner and Kordass compared mechanical and virtual articulators by analyzing contact point patterns at maximum intercuspation, but did not analyze individual condylar or other articulator settings in detail and did not test alterations to those settings, finding no significant difference between the mechanical and virtual articulators .…”
mentioning
confidence: 99%
“…In another study by the same group, two virtual articulation methods were investigated: conventional mounting and interocclusal record articulation. The authors concluded that interocclusal records resulted in decreased interarch and interocclusal distances predisposing toward infra‐occluded prostheses, whereas mounted models were associated with increased interarch and interocclusal distances 35,36 …”
Section: Step 2: Accurate Occlusal Registration In Maximum Intercuspamentioning
confidence: 99%
“…Digital workflows can be divided into 2 methods: scanning casts using a desktop scanner or scanning directly within the patient's oral cavity using an intraoral scanner . The former method involves the error of impression and gypsum materials because casts are fabricated through conventional impressions . However, because it scans outside the mouth, it is stable and high accuracy scan data can be obtained through the desktop scanner .…”
mentioning
confidence: 99%
“…The former method involves the error of impression and gypsum materials because casts are fabricated through conventional impressions . However, because it scans outside the mouth, it is stable and high accuracy scan data can be obtained through the desktop scanner . The latter method is not affected by impression and stone materials because it uses an intraoral scanner, and scan data can be obtained faster .…”
mentioning
confidence: 99%